11+m=9

Simple and best practice solution for 11+m=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11+m=9 equation:


Simplifying
11 + m = 9

Solving
11 + m = 9

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + m = 9 + -11

Combine like terms: 11 + -11 = 0
0 + m = 9 + -11
m = 9 + -11

Combine like terms: 9 + -11 = -2
m = -2

Simplifying
m = -2

See similar equations:

| 5.6x^2+40x+400=0 | | 9007-5667=x | | -2y-1(3y-9)=7+9(-3-y) | | X+7x+4=172 | | -3x=-32x+151 | | x^2-mx=32 | | 1x+5(-5)=-23 | | 7x+0=4 | | 7x+0=4 | | 7-m=m+4 | | 4x(4-5)= | | 3=23-f | | 8=b-5 | | 8(-4x+16)= | | 9s+9=-45 | | 2.3=p-0.6 | | 8(-4+16)= | | 8x+80=344 | | -7.95+X=14.95 | | 42=31-7(5-4w) | | K+(-8)=11 | | Log(6)(3x+8)=4 | | 82.5-2.25+2x=338.5 | | 2x+8=sqrt(x+4) | | 9z+15-2z= | | 2(0.5x+7)-3(2.5x+8)= | | -8x=5x-9 | | 9x^3+60x^2-21x=0 | | 2n+(2n+1.2)=4n+(2n+0.2) | | 9x^2+10x-2=0 | | (p-2)(p+4)+(p-2)(p+6)=0 | | 3/4c+3=12 |

Equations solver categories